Whitefly (Bemisia tabaci) infestation in common bean (Phaseolus vulgaris) genotypes - Marques, Miriam de Almeida; Millene Gomes de Souza (Brazilian Journal of Science, 2022)
The whitefly (Bemisia tabaci) is considered the main pest of the common bean (Phaseolus vulgaris) due to the economic damage caused to the crop by the intense suction of sap and transmission of the virus in the plants. Preventive methods of whitefly control, such as plant resistance, should be used in order not to allow the insect population to grow in crops. In this sense, the aim of this study was to evaluate the infestation of B. tabaci nymphs and adults in different common bean genotypes aiming at controlling the pest. The experiment was conducted under field conditions in the experimental area of ​​Centro Universitário de Goiás - UNIGOIÁS. The bean genotypes analyzed were: BRS Estilo, BRS FC 104, BRS Rouxinol and BRS Valente. At seventeen, twenty-four, thirty-two, thirty-nine and forty-five days after planting the bean plant, the number of whitefly nymphs and adults in the upper third of the plants was evaluated weekly. On all evaluation dates, there was a greater infestation of nymphs than adults of B. tabaci in all bean genotypes analyzed. There was a significant difference in nymph infestation between the analyzed genotypes only from the third date of insect evaluation onwards. As for the infestation of adults, the common bean genotypes differed only on the fourth date of evaluation. The BRS Rouxinol bean genotype was the one that most reduced the infestation of nymphs and adults of Bemisia tabaci, presenting characteristics of resistance and potential to control the insect.